The role of ultrasound methods in the assessment of biometric characteristics of the optic nerve - T. N. Kiseleva; A. V. Baeva; E. K. Eliseeva; V. V. Makukhina (Российский офтальмологический журнал, 2020)
The diagnostics of the optic nerve (ON) pathology relies on the results of clinical and instrumental examinations, electrophysiological tests, computer tomography and magnetic resonance imaging. The potentials of these techniques are often limited, and the costs high. Ultrasound examination  is noninvasive, informative and relatively inexpensive. The literature review is focused on the role of echography in the diagnosis and diagnostic differentiation of optic nerve pathologies. The data on the techniques of measurements  of the optic nerve sheath diameter (ONSD) and its normal parameters are presented. In addition to eye pathology, B-scanning of the optic nerve is a very useful diagnostic method in cerebral pathology and systemic diseases. In clinical practice, the measurement  of the main acoustic and biometric characteristics of ON plays a crucial role in the assessment of severity of damage and treatment effectiveness of ON pathology. The comparability of measurements of intraocular and retrobulbar ON parts using the different imaging techniques will require further studies.